2006
DOI: 10.1523/jneurosci.4194-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

The Role of CA3 Hippocampal NMDA Receptors in Paired Associate Learning

Abstract: The hippocampus is necessary for declarative memory in humans and episodic memory in rodents. Considerable current research is focused on the role of plasticity within specific subfields of the hippocampus. Here, using a viral vector to temporally control a focal deletion of the NR1 gene, we show that learning novel paired associations between specific cues and their context is dependent on CA3 NMDA receptors. Deletion of CA3 NR1 genes in Ͻ30% of the dorsal hippocampus was sufficient to disrupt new learning, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
92
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(102 citation statements)
references
References 38 publications
10
92
0
Order By: Relevance
“…This involved unilateral infusion of an adenoassociated virus vector for Cre recombinase (AAV-Cre), into our mice, in which the gene for the NMDA receptor essential subunit NR1 was ''floxed'' (fNR1 mice). This approach, which minimizes potential developmental effects of the gene deletion, has been shown to cause a selective, functional removal of NMDAr-mediated synaptic transmission and plasticity, and a behavioral deficit in new learning in a paired associate task (Rajji et al, 2006). We observed that infusion of AAV-Cre into CA3 completely blocked the novelty-enhancement of beta2 oscillations (Fig.…”
Section: Ca3 Nmda Receptors Are Required For Novelty-evoked Oscillationsmentioning
confidence: 63%
See 2 more Smart Citations
“…This involved unilateral infusion of an adenoassociated virus vector for Cre recombinase (AAV-Cre), into our mice, in which the gene for the NMDA receptor essential subunit NR1 was ''floxed'' (fNR1 mice). This approach, which minimizes potential developmental effects of the gene deletion, has been shown to cause a selective, functional removal of NMDAr-mediated synaptic transmission and plasticity, and a behavioral deficit in new learning in a paired associate task (Rajji et al, 2006). We observed that infusion of AAV-Cre into CA3 completely blocked the novelty-enhancement of beta2 oscillations (Fig.…”
Section: Ca3 Nmda Receptors Are Required For Novelty-evoked Oscillationsmentioning
confidence: 63%
“…In addition, the widespread connections of interneuron networks play a critical role in synchronizing oscillatory activity throughout hippocampus (Buzsáki, 2006). Altered NMDA function in interneuron populations with divergent connections may explain why we observed a substantial decrease in beta2 oscillations in both CA1 and CA3, following a viral manipulation that disrupted NMDA receptors in only a limited portion of the septo-temporal extent of CA3 (10-30%; Rajji et al, 2006). The same viral manipulation, when given bilaterally, is sufficient to disrupt new learning (Rajji et al, 2006).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The CA3 region of the dorsal hippocampus is preferentially associated with acquisition, whereas the CA1 region is associated with retrieval of contextual fear memory (Lee and Kesner, 2004). Furthermore, studies suggest that it is the NMDA receptors in the CA3 region, particularly in the dorsal hippocampus, that are involved in the rapid, onetrial encoding of complex associations between contextual stimuli (Cravens et al, 2006;Rajji et al, 2006).…”
Section: Estrone and Estradiol Increase Synaptophysin Expression In Tmentioning
confidence: 99%
“…In this study, animals learned which of two stimulus items (what) was rewarded depending on the environmental context (where) in which the items were presented (Rajji et al 2006;Manns and Eichenbaum 2009). On each trial, a rat initially explored one of the two contexts, after which the two stimulus items were placed into different positions (corners) of the context (Fig.…”
mentioning
confidence: 99%